EFFECTS OF THE GOVERNMENT POLICIES ON THE VARIATION OF CAR IMPORTS IN ECUADOR - Aguilar Jaramillo, Wilson (2017)
The objective of this research is to analyze the impact of the quantitative quotas imposed by the current Government, and their effect on imports of vehicles in the country. As a first step, the Pearson correlation matrix was performed where some variables such as Gross Domestic Product, quarterly sales, average sale price and oil price were introduced. This was followed by a multiple regression model based on a Log- Log that allowed to observe the variation imports of cars have when the GDP and the quarterly sale of cars change. The results show that there is some impact on imports when the state inserts policies such as quantitative quotas generate a decrease in imports and consequently a fall in vehicle sales.